Peningkatan Keterampilan Membaca Nyaring Melalui Media Cerita Bergambar Siswa Sekolah Dasar - Hidayatullah, Alfa; Haslinda; Rahmatiah (Jurnal Riset Evaluasi Pendidikan, 2024)
Improving Reading Aloud Skills through Picture Story Media for Class II Students at SDN 10 GU, Central Buton Regency, Southeast Sulawesi Province. Thesis, Department of Primary School Teacher Education, Faculty of Teacher Training and Education, Muhammadiyah University of Makassar. Supervisor 1 Haslinda and supervisor 2 Rahmatiah. The aim of the research is to improve Reading Aloud skills through Picture Story Media for Class II Students at SDN 10 GU, Central Buton Regency, Southeast Sulawesi Province. The type of research used in this research is classroom action research (PTK). The place and time of this research was at SDN 10 GU, Central Buton Regency on April 22 2024. The research subjects used in this research were 15 grade 2 students. The data collection techniques used in this research were observation, tests and documentation. The results of the research show that improving reading aloud skills through picture story media in class II students at SDN 10 GU, Central Buton Regency can be applied. This can be seen in the average value of learning outcomes in cycle I, namely that there were no students (0%) who completed reading aloud through picture story media in the SDN 10 GU class in Central Buton Regency and in cycle II there were 15 students (100%) who complete understanding of Reading Aloud Skills through Picture Story Media for Class II Students of SDN 10 GU, Central Buton Regency, Southeast Sulawesi Province.